2021
DOI: 10.1097/cm9.0000000000001864
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir vs. entecavir on recurrence of hepatitis B virus-related hepatocellular carcinoma beyond Milan criteria after hepatectomy

Abstract: Background:Hepatectomy for hepatocellular carcinoma (HCC) beyond the Milan criteria is shown to be beneficial. However, a high rate of post-operative HCC recurrence hinders the long-term survival of the patients. This study aimed to investigate and compare the impacts of tenofovir (TDF) and entecavir (ETV) on the recurrence of hepatitis B viral (HBV)-related HCC beyond the Milan criteria.Methods:Data pertaining to 1532 patients who underwent hepatectomy and received antiviral therapy between January 2014 and J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 35 publications
(88 reference statements)
2
17
0
Order By: Relevance
“…TDF was associated with a lower risk of recurrence compared to ETV [unadjusted HR (uHR) 0.88, 95% CI 0.80–0.97; I 2 = 44.9%] with a low heterogeneity among the studies (Figure S1). On pooling the aHR reported in 7 studies, 18,19,21,22,24–26 TDF was still associated with a lower risk of recurrence (aHR 0.73, 95% CI 0.65–0.81; I 2 = 67.7%), but with a moderate heterogeneity (Figure 2). Concerning the timing of recurrence reported in 5 studies, 19–21,23,25 TDF reduced the risk of late recurrence compared to ETV (aHR 0.58, 95% CI 0.45–0.76; I 2 = 0.0%) but not early recurrence (aHR 0.88, 95% CI 0.76–1.02; I 2 = 34.8%) (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…TDF was associated with a lower risk of recurrence compared to ETV [unadjusted HR (uHR) 0.88, 95% CI 0.80–0.97; I 2 = 44.9%] with a low heterogeneity among the studies (Figure S1). On pooling the aHR reported in 7 studies, 18,19,21,22,24–26 TDF was still associated with a lower risk of recurrence (aHR 0.73, 95% CI 0.65–0.81; I 2 = 67.7%), but with a moderate heterogeneity (Figure 2). Concerning the timing of recurrence reported in 5 studies, 19–21,23,25 TDF reduced the risk of late recurrence compared to ETV (aHR 0.58, 95% CI 0.45–0.76; I 2 = 0.0%) but not early recurrence (aHR 0.88, 95% CI 0.76–1.02; I 2 = 34.8%) (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…The search strategy yielded 769 records, of which nine studies [18][19][20][21][22][23][24][25][26] were included in the final analysis. Figure 1 shows the PRISMA flowchart for the study selection and inclusion process.…”
Section: Study Characteristics and Study Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The roles of serum zinc (Zn) and methallothionein in acute versus chronic hepatitis C virus (HCV) [4], are shown in Figure 1. IFN-L3 is a proinflammatory cytokine, which has shown a potent antiviral activity against both acute and chronic infections [81]. In a recent study, zinc (Zn) was found to IFN-L3 is a proinflammatory cytokine, which has shown a potent antiviral activity against both acute and chronic infections [81].…”
Section: Zinc (Zn)mentioning
confidence: 99%
“…IFN-L3 is a proinflammatory cytokine, which has shown a potent antiviral activity against both acute and chronic infections [81]. In a recent study, zinc (Zn) was found to IFN-L3 is a proinflammatory cytokine, which has shown a potent antiviral activity against both acute and chronic infections [81]. In a recent study, zinc (Zn) was found to cause an inhibition of the IFN-L3 binding to its receptor (IFNLR1).…”
Section: Zinc (Zn)mentioning
confidence: 99%